Question 7:
Jason's error occurred in Step 2. When he factored \( x^2 - 4x - 12 \), he should have factored it as \( (x - 6)(x + 2) \) correctly, but the mistake is that the product is incorrect: \( (x - 6)(x + 2) \) expands to \( x^2 - 4x - 12 \) correctly, but it implies incorrect roots when finding values that equal 0 in Step 3 and 4. He miscalculated the roots, leading to incorrect answers.
Question 8:
To solve the equation \( x^2 + 3x - 10 = 0 \) by factoring, we look for two numbers that multiply to \(-10\) (the constant term) and add to \(3\) (the coefficient of the linear term). The numbers \(5\) and \(-2\) fit these criteria.
Factoring the equation gives us: \[ (x + 5)(x - 2) = 0 \]
Setting each factor to zero gives us the solutions:
- \( x + 5 = 0 \) → \( x = -5 \)
- \( x - 2 = 0 \) → \( x = 2 \)
Therefore, the correct responses are:
- x = -5
- x = 2